Book Review: Multi-tier Supply Chain Visibility in the Automotive Industry - Bishwajit Banik Pathik; Dr. Md. Mamun Habib (International Journal of Supply Chain Management, 2013)
This book investigates how to integrate intra-and inter organizational automotive supply chain entities into a holistic supply chain visibility (SCV) system which can be established in automotive supply chains for creating performance improvements in collaboration, delivery of high performance and efficiency. The theoretical part of the book clarifies the fundamentals of SCV assessing the existing technological developments from the electronics industry as well as general implications of information sharing and transparency on corporate performance. It also explains the current economic pressures, principal supply chain structures and efforts for creating supply chain visibility in the automotive industry. The foregoing theoretical findings with a practical analysis of an automotive engine supply chain as a case study is also united at the empirical part of this book. The author presents a practical framework entitled Virtual Command Center for the electronics industry to the particular requirements of the automotive industry which describes major drivers, goals, barriers and implications of automotive supply chain visibility (SCV).